Ageing of plasma-treated poly(tetrafluoroethylene) surfaces - Nakamatsu, J.; Delgado-Aparicio, L.F.; da Silva, R.; Soberón, F. (Brill, 1999)
Highly hydrophobic poly(tetrafluoroethylene) (PTFE) surfaces were modified with an air glow discharge plasma to improve their wettability. However, the hydrophilic character obtained diminishes with time, due to molecular movement in the polymer. We have determined that the ageing process is strongly affected by the environment and temperature in which the surfaces are stored. A hydrophobic environment and high temperatures promote faster recovery of the original properties of PTFE than low temperatures. Nonetheless, a hydrophilic environment, even at high temperatures, prevents the surface from losing the polar character obtained from the plasma treatment, stopping the ageing process. Moreover, this process is reversible since the character of the treated surface changes when the environment changes (i.e. from water to air). The hydrophilicity of the surfaces was evaluated by contact angle measurements of a droplet of water.
Keywords: Tetrafluoroethylene; Wetting; Materials science; Contact angle; Glow discharge; Plasma; Polymer; Chemical engineering; Water repellent; Surface modification; Polymer chemistry; Composite material; Copolymer; https://purl.org/pe-repo/ocde/ford#2.05.01